Микроспоридия Nosema tabani sp. n. (Microsporidia, Nosematidae) из личинок слепней Украины - Левченко, Н.Г.; Андреева, Р.В. (Вестник зоологии, 1982)
Nosema tabani sp. n. differs from other species by the shape and size of spores: fresh spores 2.6-3.8X13 um, macrospores 5.1-6.4X2.6 Mm. The new species occurs in different parts of the Ukraine, causing pathological changes in the fat body of its host larvae, Tabanus autumnalis L.